Acaricidal activity, mode of action, and persistent efficacy of selected essential oils on the poultry red mite (Dermanyssus gallinae). (April 2020) - Tabari, Mohaddeseh Abouhosseini; Rostami, Arash; Khodashenas, Aref; Maggi, Filippo; Petrelli, Riccardo; Giordani, Cristiano; Tapondjou, Léon Azefack; Papa, Fabrizio; Zuo, Yanting; Cianfaglione, Kevin; Youssefi, Mohammad Reza
Abstract: In this work, the essential oils (EOs) from Litchi chinensis, Clausena anisata, Heracleum sphondylium, Pimpinella anisum, Lippia alba, Crithmum maritimum and Syzygium aromaticum were tested for their contact toxicity against the poultry red mite, Dermanyssus gallinae, a deleterious ectoparasite of aviary systems. In addition, in order to give insights on their mode of action and effectiveness, the vapor phase and residual toxicity tests were also performed. Results showed that amongst all the tested EOs, that of S. aromaticum demonstrated the highest contact toxicity, with a LC50 value of 8.9 μg/mL, followed by C. maritimum and L. chinensis EOs, with LC50 values of 23.7 and 24.7 μg/mL, respectively. L. chinensis and C. anisata EOs showed higher vapor toxicity than the other EOs. L. chinensis and S. aromaticum EOs showed promising toxic effects up to 4 days post-application. Taken together, these results highlighted L. chinensis and S. aromaticum as two promising sources of biopesticides, able to cause severe contact, vapor and residual toxicity in the poultry red mites. Given the wide plant cultivation and uses in foodstuffs, cosmetics, flavour and fragrances, these EOs may be considered cheap and ready-to-use products as valid, eco-friendly alternatives to pesticides currently used in the aviary systems. Graphical abstract: Image 1 Highlights: Dermanyssus gallinae is a deleterious ectoparasite of aviary systems. Plant essential oils are valid alternatives in the control of poultry mite. Syzygium aromaticum demonstrated the highest contact toxicity. Litchi chinensis and Clausena anisata showed higher vapor toxicity. L. chinensis and S. aromaticum showed toxic effects up to 4 days post-application.